Optimization of Targeting Rocket Launchers with Wheeled Robots - Anggara Trisna Nugraha; Alwy Muhammad Ravi; Dadang Priyambodo (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA and IKATEMI, 2021)
The quick launch weapon system is unique. This rocket launcher has a high launch rate, but the rocket launched is one stage lower than the launcher normally launched by ships of this size. For example, a (medium) cruiser would use a fast light rocket launcher to launch a light (small) rocket. Currently rocket launchers are still controlled by humans, using PCs and servo motors as control tools to determine the accuracy of the shooting angle, so complete components are needed when designing the robot so that the robot can work automatically as needed. For the input given, Automatically control the rocket launcher robot and communicate via PC, then use a USB TTL cable to forward commands to the microcontroller, then send it to the Xbee-pro transmitter circuit, then send and receive by the Xbee-pro receiver, and then send the Microcontroller for transmitter control sent to servo and rocket motors in the transmitter control system in the form of a relay. Based on the test results, the robot can guide the rocket launcher at a predetermined angle, and can launch manual rockets, multiple rockets, triple rockets and all rockets, with a success rate of up to 80%.